A mixed chloride/trifluoromethanesulfonate ligand species in a ruthenium(II) complex. (28th August 2013) - Santiso‐Quinones, Gustavo; Rodriguez‐Lugo, Rafael E.
<x xml:space="preserve">Abstract</x> The compound [2‐(aminomethyl)pyridine‐κ2N, N′][chlorido/trifluoromethanesulfonato(0.91/0.09)][(10, 11‐η)‐5H‐dibenzo[a, d]cyclohepten‐5‐amine‐κN](triphenylphosphane‐κP)ruthenium(II) trifluoromethanesulfonate dichloromethane 0.91‐solvate, [Ru(CF3SO3)0.09Cl0.91(C6H8N2)(C15H13N)(C18H15P)]CF3SO3·0.91CH2Cl2, belongs to a series of RuII complexes that had been tested for transfer hydrogenation, hydrogenation of polar bonds and catalytic transfer hydrogenation. The crystal structure determination of this complex revealed disorder in the form of two different anionic ligands sharing the same coordination site, which other spectroscopic methods failed to characterize. The reduced catalytic activity of the title compound was not fully understood until the crystallographic data provided evidence for the mixed ligand species. The crystal structure clearly shows that the majority of the synthesized material has a chloride ligand present. Only a small portion of the material is the expected complex [RuII(OTf)(ampy)(η2‐tropNH2)(PPh3)]OTf, where OTf is triflate or trifluoromethanesulfonate, ampy is 2‐(aminomethyl)pyridine and tropNH2 is 5H‐dibenzo[a, d]cyclohepten‐5‐amine.